Reliability and Significance of Forensic Anthropology in Personal Identification in Comparison with DNA Profiling Technique in South Indian Population Using Case Studies (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Identification of a decomposed dead body is a universal problem for police agencies in all countries. The method of identification relied on in a country may vary based on the established identification techniques in its forensic sciences laboratories. The DNA profiling and the skull-photograph superimposition (SPS) are the two techniques employed in forensic laboratories to identify the decomposed human heads recovered from scenes of crime. While identification through DNA profiling is unambiguous and hence conclusive, SPS seem to provide only a probable opinion. Hence, SPS technique is considered only second to DNA profiling due to its inability to establish ‘matchless’ identity. For instance, similarities of the facial features of the victim to his/her siblings and close relatives pose a major challenge in conclusively establishing the identity of the victim. Since the Court of Law admits only conclusive evidences rather than probable opinions, experts from Forensic Anthropology Unit in forensic science laboratories often face difficult situations defending results based on SPS techniques. Though it might appear as if DNA profiling would fulfil the requirements of identification in all the cases, it is not so in many instances. In many vital cases, DNA profiling has also failed in providing corroborative evidence. This paper highlights the significance of Forensic Anthropology Unit by exploring its definite role in the identification of victims in various cases in different situations with case studies.
Keywords: DNA profiling; decomposed human